A Study on the Functional Spectacle Lens with Photochromic, UV Blocking and Polarization - Hee Han, Doo (International Journal of Engineering and Technology, 2018)
Background/Objectives: It is necessary to secure competitiveness through the development of functional spectacle lens due to low cost of Chinese glasses lens and sluggish domestic glasses lens industry.Methods/Statistical analysis: A taping method was used to develop a polarized spectacle lens that partially blocks ultraviolet and blue light and has photochromic properties.Findings: The photochromic properties of the fabricated lens showed a recovery time of about 0.5 seconds for dark reaction and about 3 seconds for dark reaction. Also, the polarization ability was about 95%. Ultraviolet rays were almost shut off and blue light was reduced by about 30%. Lenses combining photochromic, UV blocking and polarizing functions are the first attempts at researching the market for spectacle lenses in Korea.Improvements/Applications: The developed lens can dramatically reduce glare caused by late night operation or reflected light with a functional lens. It serves as a sunglass for outdoor use with strong ultraviolet rays, and can be used as a spectacle lens at normal times.
Keywords: spectacle lens; sun glass; polarization; UV; blue light.